The Analysis of Individuals’ Behavioral Intention in Using Mobile Banking Based on TPB, TAM and Perceived Risk - Magdalena, Ruth; Baridwan, Zaki (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study examines the influence of subjective norms, attitude, perceived risk, perceived usefulness and perceived ease of use on individuals’ behavioral intention in using mobile banking in Brawijaya University of Malang city. The independent variables in this study are subjective norms, attitude, perceived risk, perceived usefulness and perceived ease of use. Behavioral intention in using mobile banking is a dependent variable. The study to test the hypotheses on First Order Construct (FOC) used Partial Least Square (PLS) with sample are 305 peoples. Finally, the results found that subjective norms, attitude, perceived usefulness and perceived ease of use has a positive effect towards individuals’ behavioral intention in using mobile banking. Therefore, behavioral intention of individuals to mobile banking will determine the consumer's decision to engage transaction or not. Lack of intention to use mobile banking will reduce the willingness of individuals to do bank transaction. Keywords: Subjective Norms, Attitude, Perceived Risk, Perceived Usefulness, Perceived Ease of Use, Individuals’ Behavioral Intention and Mobile Banking.